Girl Child Education for Sustainable Development Goals in Northern Nigeria - Adamu Mahuta, Salihu (MultiTech Publisher, 2023)
The paper focuses the education of the girl child in Northern Nigeria. It is an attempt to re awaken the minds of humanity on the undisputable importance of girl child education in Northern Nigeria. This paper discusses the concept of education in the northern Nigeria as well as factors militating against the objective of girl child in Northern Nigeria. The paper also makes suggestions and recommendation on how to improve the education of the girl child in the area of focus (Northern Nigeria).